JPN Guidelines for the management of acute pancreatitis: diagnostic criteria for acute pancreatitis - Koizumi, Masaru (Springer-Verlag, 2006)
The currently used diagnostic criteria for acute pancreatitis in Japan are presentation with at least two of the following three manifestations: (1) acute abdominal pain and tenderness in the upper abdomen; (2) elevated levels of pancreatic enzyme in the blood, urine, or ascitic fluid; and (3) abnormal imaging findings in the pancreas associated with acute pancreatitis. When a diagnosis is made on this basis, other pancreatic diseases and acute abdomen can be ruled out. The purpose of this article is to review the conventional criteria and, in particular, the various methods of diagnosis based on pancreatic enzyme values, with the aim of improving the quality of diagnosis of acute pancreatitis and formulating common internationally agreed criteria. The review considers the following recommendations: — Better even than the total blood amylase level, the blood lipase level is the best pancreatic enzyme for the diagnosis of acute pancreatitis and its differentiation from other diseases. — A pivotal factor in the diagnosis of acute pancreatitis is identifying an increase in pancreatic enzymes in the blood. — Ultrasonography (US) is also one of the procedures that should be performed in all patients with suspected acute pancreatitis. — Magnetic resonance imaging (MRI) is one of the most important imaging procedures for diagnosing acute pancreatitis and its intraperitoneal complications. — Computed tomography (CT) is also one of the most important imaging procedures for diagnosing acute pancreatitis and its intraabdominal complications. CT should be performed when a diagnosis of acute pancreatitis cannot be established on the basis of the clinical findings, results of blood and urine tests, or US, or when the etiology of the pancreatitis is unknown. — When acute pancreatitis is suspected, chest and abdominal X-ray examinations should be performed to determine whether any abnormal findings caused by acute pancreatitis are present. — Because the etiology of acute pancreatitis can have a crucial influence on both the treatment policy and severity assessment, it should be evaluated promptly and accurately. It is particularly important to differentiate between gallstone-induced acute pancreatitis, which requires treatment of the biliary system, and alcohol-induced acute pancreatitis, which requires a different form of treatment.